2023
DOI: 10.3390/v15020559
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Hepatocellular Carcinoma in Patients with Chronic Hepatitis Virus Infection

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths globally. The risk factors for HCC include chronic hepatitis B and C virus infections, excessive alcohol consumption, obesity, metabolic disease, and aflatoxin exposure. In addition to these viral and environmental risk factors, individual genetic predisposition is a major determinant of HCC risk. Familial clustering of HCC has been observed, and a hereditary factor likely contributes to the risk of HCC development. The famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 99 publications
1
3
0
Order By: Relevance
“…Our study revealed a significant increase in serum copper levels in patients infected with hepatitis C virus (HCV) compared to the control group table (6),This finding is consistent with previous studies conducted by 34,45 ,which found elevated copper levels in patients with chronic viral hepatitis. Serum copper increases in response to acute HCV infection; this effect is heightened in CHC and fibrotic liver disease.…”
Section: Crsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study revealed a significant increase in serum copper levels in patients infected with hepatitis C virus (HCV) compared to the control group table (6),This finding is consistent with previous studies conducted by 34,45 ,which found elevated copper levels in patients with chronic viral hepatitis. Serum copper increases in response to acute HCV infection; this effect is heightened in CHC and fibrotic liver disease.…”
Section: Crsupporting
confidence: 92%
“…These findings corroborated those of 35,36,37 ,whose reported that individuals with chronic hepatitis C had significantly lower zinc concentrations than healthy control groups when zinc concentrations were examined at the level of the whole body. In the present study Serum copper levels were found to be significantly increased in all patient groups compared to the control group (P<0.05), table (6). Copper is known to be essential in the proper functioning of various metal enzymes, including ceruloplasmin involved in iron metabolism 38 .…”
Section: Crsupporting
confidence: 50%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC), as the sixth most common tumor in the world, is currently the fourth leading cause of cancer-related mortality [ 1 , 2 ]. According to the most recent epidemiological information, HCC is closely associated with the following risk factors: infection with the hepatitis virus, exposure to Aflatoxin, non-alcoholic fatty liver disease, excessive alcohol intake, and obesity [ 3 , 4 ]. At present, the main treatment methods for liver cancer include surgical resection, liver spread, thermal expansion, intra-arterial, radiation and systemic therapies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary hepatocellular carcinoma (HCC) is a prevailing malignant tumor, and represents a major health-care challenge in the population ( 1 ). Previous research suggests that primary HCC is associated with genetic factors, alcoholism, obesity, viral infections, and metabolic diseases ( 2 , 3 ). Currently, surgical treatment is the main treatment strategy for primary HCC.…”
Section: Introductionmentioning
confidence: 99%